Dampak Strategi Marketing Syariah dalam Menghadapi Persaingan Bisnis Waralaba : Studi Kasus di Mini Market Tifany Kecamatan Muara Bulian - Reza Hafiza Rahim; Hansen Rusliani; Refky Fielnanda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This thesis aims to determine the competition of the Tifany mini market business with other modern markets in Muara Bulian sub-district and to determine the marketing strategy of the Tifany Mini Market to survive the competition of the modern market in Muara Bulian sub-district. This study uses a qualitative approach with data collection methods by conducting observations, interviews, documentation and drawing conclusions. The results of the research conclusions obtained from interviews with informants revealed that, 1) the competition in the retail business in the city of Muara Bulian Jambi is indeed very tight, this is because more modern retailers have emerged such as Alfamart and Indomart, so that retailers from the area themselves must be ready to compete, 2) What makes the Tifany Mini Market survive in the midst of the booming modern retail business is in the success of the Tifany Mini Market, the first thing to do is to maintain product quality, in addition to the quality of service and trust in consumers for loyal customers are allowed to be in debt so that consumers remain loyal to the Tifany Mini Market. In addition, continuing to add appropriate and more adequate facilities so that customers feel safe and comfortable when they are in the store and supported by a strategic location makes the Tiffany Mini Market able to successfully survive and compete amidst the booming retail business.